Riba dan Bunga Bank - Budiman, Muhammad Fajar Aditya Putra; Rezki, Muhammad; Setyanoor, Erwan (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
This study aims to examine the concept of riba and bank interest and to analyze their similarities and differences from the perspective of Islamic economics. Riba refers to an additional charge stipulated in lending transactions and is strictly prohibited in Islam because it is considered unjust and harmful to society. Meanwhile, bank interest is a compensation system applied in conventional financial institutions as a return for the use of funds. This research employs a qualitative method with a literature review approach by analyzing books, scientific journals, and credible sources related to riba and bank interest. The results of the study indicate that the majority of Islamic scholars equate bank interest with riba due to the existence of predetermined additional payments that may lead to economic inequality. Therefore, Islamic banking emerges as an alternative financial system that applies profit-sharing principles and contracts in accordance with Islamic law. The conclusion of this study is that riba and bank interest are fundamentally similar in practice from the Islamic perspective, making Islamic financial systems a more ethical and just solution.